2007
DOI: 10.1186/1471-2148-7-117
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA analysis of field populations of Helicoverpa armigera (Lepidoptera: Noctuidae) and of its relationship to H. zea

Abstract: Background: Helicoverpa armigera and H. zea are amongst the most significant polyphagous pest lepidopteran species in the Old and New Worlds respectively. Separation of H. armigera and H. zea is difficult and is usually only achieved through morphological differences in the genitalia. They are capable of interbreeding to produce fertile offspring. The single species status of H. armigera has been doubted, due to its wide distribution and plant host range across the Old World. This study explores the global gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
185
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(225 citation statements)
references
References 59 publications
29
185
1
5
Order By: Relevance
“…The Australian H. armigera data set consisted of 16 females from Dalmore, Victoria (38º11′S, 145º25′E) and 10 females from Orbost, Victoria (37º42′S, 148º27′E), both of which come from samples from the work by Behere et al (2007) and a new collection of 112 females from MacIntyre Valley, Queensland (28º32′S, 150º18′E). The three collection sites are all temperate agricultural regions.…”
Section: Samplesmentioning
confidence: 99%
See 4 more Smart Citations
“…The Australian H. armigera data set consisted of 16 females from Dalmore, Victoria (38º11′S, 145º25′E) and 10 females from Orbost, Victoria (37º42′S, 148º27′E), both of which come from samples from the work by Behere et al (2007) and a new collection of 112 females from MacIntyre Valley, Queensland (28º32′S, 150º18′E). The three collection sites are all temperate agricultural regions.…”
Section: Samplesmentioning
confidence: 99%
“…We initially characterized five loci for which Z-linkage was determined by pedigree analyses (Apt, Cyp303a1, Period, Phc and Tpi) in two Victorian population samples described by Behere et al (2007 Table S3), which suggested that LD analyses could be conducted on alleles pooled from all three populations (see below). Levels of nucleotide diversity across all loci and the three Australian collection sites were high (694 single-nucleotide polymorphisms in o6 kb of sequence) and did not differ substantially between collection sites for any locus (Table 1).…”
Section: Sequence Diversitymentioning
confidence: 99%
See 3 more Smart Citations